Opinions of Teachers on Distance Education Applications in English Language Teaching Policies in Northern Cyprus During the COVID-19 Pandemic - Uysal, Merve; Çağanağa, Çağda Kıvanç (Frontiers in Psychology, 2022)
The Covid-19 pandemic affected education institutions just like several other sectors. These institutions, which are among the places where people are found collectively, were the first places that were closed for precaution. Some problems of distance education conducted in online platforms which were assumed upon the termination of face-to-face education emerged in time. Especially in this urgent solution, where the workload of teachers has increased, some application difficulties have been identified in foreign language teaching. From this point of view, considering the foreign language education policy and planning, this study deals with the distance education practices of English teachers, the difficulties they encounter in the process, and their solution proposals. The research, which was designed as a qualitative study, was conducted with a case study design. The participants of the research are 13 English teachers working at the secondary school level in different districts of Northern Cyprus determined by the homogeneous sampling method. The data were collected through semi-structured interviews developed by the researchers. The qualitative data were analyzed with descriptive analysis. As a result of the interviews with the teachers, it has been determined that there are problems related to technology, students, online classes, and planning in English teaching carried out with distance education applications. Accordingly, the teachers offered their recommendations that could be a solution to the existing problems.